Indo-Bangladesh Trade Potentials. - Madaan, Davinder Kumar (2013)
India and Bangladesh have a great potential of mutual trade because of their proximity, complimentarity and competitiveness to each other. The official trade of US $3306 m between the two countries in 2010 could increase to US$ 20175 m (6.1 times), if both could have removed certain irritants in the way of trade. The boost in trade requires political-will with very little investment. There exists high potential for bilateral trade in case of petroleum oils (not crude), textiles, rice, cars, leather, chemical fertilizers, jute engineering goods, transport equipments, etc. In this paper, the analysis of the potentialities of trade between India and Bangladesh has been done. The discussion, in this paper, is mainly based on trade data of both the countries during recent period of 2002-10. Projections of each country’s actual and potential imports from partner country during 2012-20 have been worked out.